2010
DOI: 10.1002/prot.22834
|View full text |Cite
|
Sign up to set email alerts
|

Structural facets of disease‐linked human prion protein mutants: A molecular dynamic study

Abstract: Prion propagation in transmissible spongiform encephalopathies involves the conversion of the cellular prion protein, PrPC, into the pathogenic conformer PrPSc. Human familial forms of the disease are linked to specific mutations in the PrP gene, PRNP, and include Gerstmann-Strussler-Scheinker syndrome (GSS), familial Creutzfeldt-Jakob disease (fCJD), and fatal familial insomnia. To gain insights into the molecular basis of these disorders, we performed 200 ns of classical molecular dynamic simulations in aque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
61
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 67 publications
8
61
0
Order By: Relevance
“…This result is also obtained for mPrP C , where the observed line broadening can be rationalized by conformational exchange between two precisely defined, locally different structures (28). There are, by now, numerous model simulations focused on the β2-α2 loop in PrP C (29)(30)(31)(32)(33), and continuation of work along these lines will greatly benefit from a more comprehensive platform of experimental data.…”
Section: T Ransmissible Spongiform Encephalopathies (Tses) Includesupporting
confidence: 53%
See 1 more Smart Citation
“…This result is also obtained for mPrP C , where the observed line broadening can be rationalized by conformational exchange between two precisely defined, locally different structures (28). There are, by now, numerous model simulations focused on the β2-α2 loop in PrP C (29)(30)(31)(32)(33), and continuation of work along these lines will greatly benefit from a more comprehensive platform of experimental data.…”
Section: T Ransmissible Spongiform Encephalopathies (Tses) Includesupporting
confidence: 53%
“…(ii) The residue position 168 is polymorphic in sheep PrP, and the residue type in this position affects susceptibility of sheep to scrapie (51)(52)(53)(54). (iii) For TSE-sensitive mutants of PrP C , molecular dynamics simulations indicate a trend for solvent exposure of Y169 (29)(30)(31)(32)(33), leading to increased hydrophobicity of the loop surface, which has been related to increased cytotoxicity of prion proteins (55,56). The conformations with exposed Y169 that are observed in the molecular dynamics simulations are similar to the type I β-turn loop conformation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The latter type of pathogenic mutation has been found in at least 28 different locations, and effects on protein stability, misfolding as well as cellular processing and function are reported [123]. MD simulations can be used to study the effect of these mutations on protein conformation and stability, particularly for the 24 mutations that are found in the C-terminal folded domain of human PrP [124][125][126]. Structural biology can also offer insights into the structural effect of pathogenic mutations [75,127] (see also chapter Y by Surewicz et al).…”
Section: The Effect Of Pathogenic Mutationsmentioning
confidence: 99%
“…Molecular dynamics (MD) simulations have provided insights into the structural determinants and the plasticity of several other variants associated with DLMs 41-53,63-68 having a large incidence in the disease, 15 as well as the protective polymorphism HuPrP(E219K-129M) [HuPrP(PP) hereinafter] ‡. 43 All of these studies have shown that the secondary and tertiary elements are similar across all these variants.…”
Section: Introductionmentioning
confidence: 99%